Beyond trauma: Decolonizing understandings of loss and healing in the Indian Residential School system of Canada. (5th June 2021) - Burrage, Rachel L.; Momper, Sandra L.; Gone, Joseph P.
Abstract: Indigenous scholars and others who study the experiences of Indigenous communities have long criticized the psychocentric approach to trauma held by most clinical professionals. A recent example of this was the Canadian government's reparations for Indian Residential School system (IRS) survivors, which focused largely on individual psychological harms rather than broader effects of colonial oppression. Beginning in 1867 and continuing throughout the latter half of the twentieth century, Indigenous children were routinely removed from their home communities in Canada and placed into the IRS system, where they were frequently subject to physical, psychological, and sexual abuse. Using thematic analysis, this study draws on survivor testimonies from one residential school to explore how their descriptions of the effects and healing from IRS abuses differ from psychocentric understandings of trauma and loss. Results indicate that survivors describe IRS effects in sociocentric, ecocentric, and cosmocentric terms more so than psychocentric ones and place deep importance on healing through connection to family, culture, and community. To decolonize itself as a discipline and better serve Indigenous communities, the field of psychology must open up to understandings of trauma, loss, and healing that decentralize the individual, a difficult task given the discipline's psychocentric nature.